A randomized controlled trial to evaluate the Make Safe Happen® app-a mobile technology-based safety behavior change intervention for increasing parents' safety knowledge and actions - Lara B. McKenzie; Kristin J. Roberts; Roxanne Clark; Rebecca McAdams; Mahmoud Abdel-Rasoul; Elizabeth G. Klein; Sarah A. Keim; Orie Kristel; Alison Szymanski; Christopher G. Cotton; Wendy C. Shields (BMC, 2018)
Abstract Background Many unintentional injuries that occur in and around the home can be prevented through the use of safety equipment and by consistently following existing safety recommendations. Unfortunately, uptake of these safety behaviors is unacceptably low. This paper describes the design of the Make Safe Happen® smartphone application evaluation study, which aims to evaluate a mobile technology-based safety behavior change intervention on parents' safety knowledge and actions. Methods Make Safe Happen® app evaluation study is a randomized controlled trial. Participants will be parents of children aged 0-12 years who are recruited from national consumer online survey panels. Parents will complete a pretest survey, and will be randomized to receive the Make Safe Happen® app or a non-injury-related app, and then complete a posttest follow-up survey after 1 week. Primary outcomes are: (1) safety knowledge; (2) safety behaviors; (3) safety device acquisition and use, and (4) behavioral intention to take safety actions. Results Anticipated study results are presented. Conclusions Wide-reaching interventions, to reach substantial parent and caregiver audiences, to effectively reduce childhood injuries are needed. This study will contribute to the evidence-base about how to increase safety knowledge and actions to prevent home-related injuries in children. Trial registration number NCT02751203; Pre-results.